Epidemiological analysis of new tuberculosis cases in a private freedom population in northeast Brazil (Research, Society and Development, 2022)
Objective: To analyze the epidemiological characteristics of new cases of tuberculosis among people deprived of liberty reported in Alagoas from 2009 to 2018. Method: This is a descriptive, retrospective epidemiological study with a quantitative approach. The study population consisted of people deprived of liberty in the state of Alagoas notified with tuberculosis in the Notifiable Diseases Information System (SINAN) from 2009 to 2018. The data explained were analyzed using descriptive statistics, based on relative and absolute frequency in percentage. Results: There was an increase in the number of new cases of tuberculosis in the prison system: 22.9% (2013), 9.3% (2016) and 13.4% (2018). Among the 411 new cases, 80.8% were male, aged between 20 and 39 years (63.5%). Regarding race/skin color, 330 (80.3%) were black/brown and 11.4% were white. Regarding the clinical characteristics of new cases of tuberculosis, the pulmonary clinical form was almost entirely, represented in 90.3% of cases. Conclusion: The results of this study lead to reflection on the need to improve the quality of care provided and to consider that if we continue with the accelerated growth of the population deprived of liberty, if we do not launch specific strategies in the prison context and treat risk factors for tuberculosis illness, it will be difficult to think about the end of tuberculosis.